Facile synthesis of ultrasmall MnFe2O4 nanoparticles with high saturation magnetization for magnetic resonance imaging. Issue 24 (15th December 2021) - Ma, Yingli; Xu, Xiaoguang; Lu, Liying; Meng, Kangkang; Wu, Yong; Chen, Jikun; Miao, Jun; Jiang, Yong
Abatract: The optimal particle size and surface states are important to superparamagnetic nanoparticles for magnetic resonance imaging (MRI) contrast agents. Here, a simple one-pot approach is proposed to prepare ultrasmall hydrophobic MnFe2 O4 superparamagnetic nanoparticles with a uniform diameter of about 4.7 nm. To satisfy the requirements for MRI contrast agents, the MnFe2 O4 nanoparticles are reduced by chitosan to form MnFe2 O4 @chitosan nanoparticles (MnFe2 O4 @CS NPs), which dramatically increases the saturation magnetization (Ms ) of the nanoparticles by 21%. The valence state analysis indicates that the amino group (NH2 ) of chitosan shares lone pair electrons with Mn 4+, resulting in high-spin state Mn 3+ to enhance the Ms . The MnFe2 O4 @CS NPs show significant signal reduction and high r2 value in the T2 -weighted imaging. Therefore, due to their large specific surface area and high responsiveness to the external magnetic field, MnFe2 O4 @CS NPs are expected to be applied to nano platform in magnetic targeting therapy with the function of MRI contrast agents in vivo.